Teaching Styles And Students’ Engagement Among Junior High Schools in Claveria Districts, Misamis Oriental (American Journal of Multidisciplinary Research and Innovation, 2025)
This study aimed to determine the effect of teachers’ teaching styles on students’ engagement. Specifically, it aimed to describe the respondents’ characteristics; find the level of the respondents’ perceived teaching style; examine the respondents’ perceived assessment of affective and cognitive engagement; find the significant effect of teaching styles on students’ engagement; and determine the relationship between teaching styles and their characteristics. In this research , a purposive sampling procedure was used to obtain the 300 public junior high school students of Claveria Districts, Misamis Oriental, during the School Year 2023-2024. A combination of patterned and self-constructed questionnaire with descriptive statistics were used, along with a T-test, to test the significant effects of teaching styles on students’ engagement. Pearson Product Moment Correlation (r) was utilized to determine the vital relationship between teaching styles and respondents’ characteristics. The study found that among all teaching styles, expert style obtained the highest mean result and interpreted as very high. The respondents perceived affective and cognitive engagement as very positive. Teaching styles, except delegator, significantly affect students’ engagement. Further, based on students’ perceptions, their parents’ marital status and educational attainment are significantly related to teaching styles. In conclusion, it is essential to identify appropriate teaching styles based on students’ backgrounds. It is recommended to help create a holistic and practical learning environment. Further studies are needed to understand school environments’ influence on teaching styles and students’ engagement.